PENGARUH STRUKTUR, PERILAKU, EFISIENSI, DAN KINERJA SEKTOR KONSTRUKSI (GO PUBLIC) DI INDONESIA - Wintra Tama Kencana; jakaria , (Media Ekonomi, 2017)
The purpose of this paper is to analyze structure, conduct, efficiency and performance of construction industry and also the effect of market share (MS), efficiency (Ef), and company size (Size) towards the Return of Asset (ROA) of construction sector (go public) in Indonesia. The method that is used is Structure, Conduct and Performance (SCP) approach. Data Envelopment Analysis (DEA) is used to analyze the efficiency of construction sector. Quantitative analysis is used to discover the structure and performance of construction sector in Indonesia. The data were obtained from the Indonesian Stock Exchange. The data obtained and used in this paper are secondary data, which includes net profit, total asset, fixed asset, revenue and labor. The period which this paper covers is 2010 – 2015 (6 years). The result of SCP analysis shows that the structure of the construction sector in Indonesia is a strict oligopoly, with the average CR4 value above 50 percent. Conduct analysis in construction sector can be cooperate with competitors, pricing and promotion. While the performance of construction sector can be seen from its ROA, efficiency (Ef), and company size.